2020
DOI: 10.1080/07391102.2020.1839564
|View full text |Cite
|
Sign up to set email alerts
|

Binding mechanism and structural insights into the identified protein target of COVID-19 and importin-α within-vitroeffective drug ivermectin

Abstract: While an FDA approved drug Ivermectin was reported to dramatically reduce the cell line of SARS-CoV-2 by ∼5000 folds within 48 h, the precise mechanism of action and the COVID-19 molecular target involved in interaction with this in-vitro effective drug are unknown yet. Among 12 different COVID-19 targets along with Importin-α studied here, the RNA dependent RNA polymerase (RdRp) with RNA and Helicase NCB site show the strongest affinity to Ivermectin amounting −10.4 kcal/mol and −9.6 kcal/mol, respectively, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 40 publications
5
43
1
1
Order By: Relevance
“…Ivermectin is a well-known antiparasitic, highly effective against helminthic infestations and with an excellent safety profile. In the past few years, studies have shown that ivermectin also has an antiviral effect on DNA and RNA viral families, preventing the virus from entering cells; promoting inhibition of the transporter complex "nuclear transporter mediated by α / β importin", fundamental to the viral replication process; and binding to RNA-dependent RNA polymerases, also leading to disruption of viral replication [ [1] , [2] , [3] , [4] ].…”
Section: Introductionmentioning
confidence: 99%
“…Ivermectin is a well-known antiparasitic, highly effective against helminthic infestations and with an excellent safety profile. In the past few years, studies have shown that ivermectin also has an antiviral effect on DNA and RNA viral families, preventing the virus from entering cells; promoting inhibition of the transporter complex "nuclear transporter mediated by α / β importin", fundamental to the viral replication process; and binding to RNA-dependent RNA polymerases, also leading to disruption of viral replication [ [1] , [2] , [3] , [4] ].…”
Section: Introductionmentioning
confidence: 99%
“…This interaction map appeared more optimized based on the distribution of interactions than predicted by docking procedures ( Figure 1A , supplementary material ). Some of the residues stabilizing IVM and mouse importin-α (Trp184, Asn228, and Trp231) were also observed in a previous theoretical study combining docking and MD simulation to monitor the prevalence of the docked complex (Sen Gupta et al, 2020 ).…”
Section: Resultsmentioning
confidence: 72%
“…Another recent study employed docking and MD simulations with the molecular mechanics Poisson-Boltzmann surface area (MMGBSA) approach to explore the affinity of IVM with importin-α and several SARS-CoV-2 targets. They identified IVM bound RdRp-RNA and Nsp13 helicase with a higher affinity than importin-α (Sen Gupta et al, 2020 ). Both studies provided critical information that can be used to provide more robust results by employing MD simulations combined with the MMGBSA approach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent molecular docking study demonstrated that in addition to IMPα, IVM showed high binding affinity to the viral RNA-dependent RNA polymerase (RdRp) complexed with RNA helicase compared to other 10 viral targets included in the analysis ( 43 ). However, it was later shown that IVM does not bind to viral RdRp in both Zika virus (Z.V.)…”
Section: Ivermectinmentioning
confidence: 99%